Transcriptome Profiling Reveals the Negative Regulation of Multiple Plant Hormone Signaling Pathways Elicited by Overexpression of C-Repeat Binding Factors - Li, Aixin; Zhou, Mingqi; Wei, Donghui; Chen, Hu; You, Chenjiang; Lin, Juan (Frontiers in Plant Science, 2017)
CBFs (C-repeat Binding Factors) are a subfamily of AP2 transcription factors that play critical roles in the regulation of plant cold tolerance and growth in low temperature. In the present work, we sought to perform a detailed investigation into global transcriptional regulation of plant hormone signaling associated genes in transgenic plants engineered with CBF genes. RNA samples from Arabidopsis thaliana plants overexpressing two CBF genes, CBF2 and CBF3, were subjected to Illumina HiSeq 2000 RNA sequencing (RNA-Seq). Our results showed that more than half of the hormone associated genes that were differentially expressed in CBF2 or CBF3 transgenic plants were related to auxin signal transduction and metabolism. Most of these alterations in gene expression could lead to repression of auxin signaling. Accordingly, the IAA content was significantly decreased in young tissues of plants overexpressing CBF2 and CBF3 compared with wild type. In addition, genes associated with the biosynthesis of Jasmonate (JA) and Salicylic acid (SA), as well as the signal sensing of Brassinolide (BR) and SA, were down-regulated, while genes associated with Gibberellin (GA) deactivation were up-regulated. In general, overexpression of CBF2 and CBF3 negatively affects multiple plant hormone signaling pathways in Arabidopsis. The transcriptome analysis using CBF2 and CBF3 transgenic plants provides novel and integrated insights into the interaction between CBFs and plant hormones, particularly the modulation of auxin signaling, which may contribute to the improvement of crop yields under abiotic stress via molecular engineering using CBF genes.